Determination of atractylon in rat plasma by a GCâMS method and its application to a pharmacokinetic study - Han Yan; Yuanyuan Sun; Yuying Ma; Bin Ji; Xiaohong Hou; Zhiguo Yu; Yunli Zhao (Elsevier, 2015)
A sensitive and selective method based on gas chromatography hyphenated to mass spectrometry (GCâMS) was developed and validated for the determination of atractylon in rat plasma. Plasma samples were processed by liquidâliquid extraction with ethyl acetate-n-hexane (1:1, v/v) using acetophenone as an internal standard (IS). Analytes were determined in selective ion monitoring (SIM) mode using target ions at m/z 108.1 for atractylon and m/z 105.1 for acetophenone. The calibration curve was linear over the concentration range of 10â1000Â ng/mL with lower limit of quantification of 10Â ng/mL. The intra- and inter-day precision variations were not more than 10.4% and 9.6%, respectively, whilst accuracy values ranged from â6.5% to 4.9%. Extraction recovery of the assay was satisfactory. This method was successfully applied to quantification and pharmacokinetic study of atractylon in rat plasma after intragastric administration of Atractylodis extract. Keywords: Atractylon, Atractylodis, Rat plasma, Pharmacokinetics, GCâMS